2011
DOI: 10.1111/j.1365-2796.2011.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease: an independent risk factor for colorectal neoplasia

Abstract: Stadlmayr A, Aigner E, Steger B, Scharinger L, Lederer D, Mayr A, Strasser M, Brunner E, Heuberger A, Hohla F, Steinwendner J, Patsch W, Datz C (Oberndorf Hospital, Oberndorf; Paracelsus Medical University, Salzburg, Austria). Nonalcoholic fatty liver disease: an independent risk factor for colorectal neoplasia. J Intern Med 2011; 270: 41–49. Abstract. Background and aims.  Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of insulin resistance (IR), and IR is associated with an increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 35 publications
5
64
0
2
Order By: Relevance
“…Studies have shown that NAFLD patients have significantly more colorectal (CR) neoplasia and early CR cancer compared to those without NAFLD (29). We did not have data available on screening for colorectal neoplasia; thus, the potential of underlying gastrointestinal bleed from undetected CR neoplasia may potentially be a cause for ID.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NAFLD patients have significantly more colorectal (CR) neoplasia and early CR cancer compared to those without NAFLD (29). We did not have data available on screening for colorectal neoplasia; thus, the potential of underlying gastrointestinal bleed from undetected CR neoplasia may potentially be a cause for ID.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and details of the clinical and biochemical work-up of included subjects have been reported previously [23]. Subjects were allocated to one of three groups: (1) lean, healthy control group (n = 53), (2) MetS without iron overload (n = 54) and (3) MetS with iron overload (n = 56).…”
Section: Methodsmentioning
confidence: 99%
“…As stated previously, patients with NAFLD have reduced levels of protective adipokines and adiponectin. Therefore, common factors among NAFLD, colon polyps and CRC include IR, chronic inflammation, oxidative stress and decreased levels of adiponectin[2,4,147,148,149,150,152]. In recent years, an increasing number of publications have identified NAFLD as an independent risk factor for the development of adenomatous polyps and CRC[147-153].…”
Section: Nonalcoholic Fatty Liver Disease and Colorectal Cancermentioning
confidence: 99%